Contract for Rotary Sweeper Broom Refills for Airport Snow Removal - INSPECTOR GENERAL DEPT OF DEFENSE ARLINGTON VA (1997)
We initiated the audit as a result of a letter from Senator Michael DeWine regarding allegations from a constituent. The constituent alleged that the Defense Supply Center, Columbus, Ohio, awarded a firm-fixed price contract for $232,010 to Danline, Incorporated (Danline), for tufted wire bush refills (tufted brushes) that was improper. The contract was improperly awarded because Danline had not demonstrated its ability to manufacture this product and a first article test required in the contract solicitation was erroneously waived. Military installations use commercial rotary broom sweepers to remove snow and ice from their airport runways. Accordingly, the broom refills must be of sufficient quality to preclude the brushes from coming apart. Loose bush material can cause catastrophic result if ingested into aircraft engines. The Defense Supply Center, Columbus manages 11 different types of rotary bush refills. From 1993 through 1996, the Defense Supply Center, Columbus procured 52,135 brush refills, totaling $923,643, from three contractors. Audit Objectives. The overall objective of the audit was to determine whether the allegations have merit.